Artificial radiofrequency driven life-table parameters of perilla seed bugs (Nysius sp.) (Heteroptera: Lygaeidae) - Maharjan, Rameswor; Yoon, Youngnam; Jang, Yunwoo; Jeong, Mihye; Jung, Tae-Wook; Suk Cho, Hyun; Yi, Hwijong (Journal of Asia-Pacific entomology, 2020)
[Display omitted] •Radiofrequency (RF) is the newly adopted technology in Korea.•The effects were compared on 0, 5, 10, 20, and 30 kHz frequencies.•The RF negatively affected the oviposition and adult performances of bugs.•The RF effect found to be transmitted into subsequent generations of bugs.•Findings were well discussed in terms of IPM as an alternative to chemicals. The genus Nysius (Hemiptera: Lygaeidae) are polyphagous pests of various plants that damage seeds, foliage, and flowers. Here, we studied the life-table parameters and adult performances of Nysius plebeius Distant and Nysius hidakai Nakatani after exposure to five radiofrequencies: 0 (control), 5, 10, 20, and 30 kHz in infested perilla seeds. In addition, we measured the follow on effects of treatment for four generations (Parent, F1-, F2-, and F3-generation), for both Nysius species. Radiofrequency application significantly affected the life-table parameters of both Nysius species. Radiofrequency exposures affected bug oviposition, developmental period, adult weight, and longevity. Exposure also negatively affected the fecundity of subsequent generations; total developmental period from egg to adult emergence was longer while adult longevity was shorter in the radiofrequency treatments than in the untreated control. Low radiofrequency levels had the greatest effect on the life-table parameters of Nysius species, with the lowest rate of adult emergence and the shortest adult longevity at 5 kHz. The potential of using Nysius bug susceptibilities to radiofrequency as an alternative to chemical treatment is discussed.